Nationaler Kulturgüterschutz und Freizügigkeit der Unionsbürger - Caldoro, Stefano (Cultural property studies., 2009)
The subject of this examination is the issue of whether and to what extent the Member States of the European Community may classify privately owned cultural assets as national cultural assets and if the transfer of such assets abroad can be prohibited if the owner of such cultural asset exercises its right of free movement. The aim of this study is to highlight the conflict between national cultural asset protection and the European directives.